Redesigning care for back pain in an Australian hospital setting: A service evaluation to identify need for change. (7th September 2022) - Gorgon, Edward; Maka, Katherine; Sullivan, Justin; Nisbet, Gillian; Hancock, Michelle; Regan, Gerard; Leaver, Andrew
Abstract: Objective: This needs assessment study examined current processes of physiotherapy care for adults with back pain in a large teaching hospital serving a multicultural community in Sydney, Australia. Evaluation of current practices is a necessary first step in the design of a patient‐centred, multidisciplinary service that promotes best practice in back pain management. Methods: We conducted a retrospective service evaluation in the physiotherapy outpatient department by reviewing clinical data on episode of care and processes of care for adults managed for back pain over a 6‐month period using a defined protocol ( n  = 252). Results: Patients (median age = 56 years; 72.2% born outside of Australia) were referred from various internal and external sources, with 79.8% having chronic back pain. The median length of episode of care was 8 weeks. Active interventions were almost universally used (98.4% of records). Key aspects of assessment were frequently recorded (84.5%–98% of records), but psychosocial risk assessment was not routinely recorded. Aspects of longitudinal management planning, including goal setting, outcome measurement, and routine follow‐up, were also not routinely recorded. Conclusions: This study demonstrated that physiotherapy processes of care in this setting followed key messages of best practice particularly with regard to interventions, in contrast to other settings and jurisdictions. However, the brief episodes of care and less evident focus on psychosocial aspects might not align with the needs of the majority with chronic back pain. These findings suggest the need to reframe processes of care with a biopsychosocial approach and structure episodes of care towards long‐term management solutions.